KNOWLEDGE AND, CONSUMPTION OF VEGETABLE FRUIT TO CONSTIPATION ON BOARDING SCHOOL STUDENTS SMAN 5 GOWA - Ghea Fricillia Sambe (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2021)
Introduction: Lack of nutritional knowledge leads to unhealthy eating habit that can cause nutritional problem in adolescence. Teenagers are more likely to consume less fiber than younger children in their diet which can make them become more vulnerable to have constipation. Purpose: This study aims to determine nutritional knowledge, consumption of vegetable and fruit and constipation of boarding school students at SMAN 5 Gowa. Material and Method: The sample was 139 students which was randomly chosen by Proportionate Stratified. The level of nutritional knowledge was measured by a form of nutritional knowledge while consumption of fruit vegetables using the 24 hour recall method. Defecation pattern was measured by using the Constipation Scoring System form. Results: Majority of students 88.5% were lacked of nutritional knowledge. Consumption of vegetables and fruits was insufficient which was only about 5.41gr in average. The incidence of constipation was low, only 4.3%. Conclusion: Nutritional knowledge as well as, consumption of vegetable and fruit were poor. Meanwhile the incidence of constipation relatively low